A Contrastive Analysis Of Prefix In English And Batak - Fifi Sidabalok; Dwi Natalia Purba; Karmila Sihombing; Anita Sitanggang (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
Indonesia is one of the big countries in the world consists of many islands which are separated by oceans and islands that has many tribes as well as their languages. One of the tribes in Indonesia is Bataknese. Batak are an ethnic group from North Sumatra. Most of Bataknese are living in North Sumatra. In this contrastive analysis, the writer chooses two languages, first, English as the source language and Batak Toba language as the target language. objectives of this study is restricted to investigating and describing the differences of the two languages about suffix in English and Toba Batak Language, that focus in prefix in meaning.This study was applied by descriptive qualitative design. The data was taken a news text with the titlle Ridwan Kamil is popular among female voters, Sandiaga Uno among male voters from kompas website.The findings describied that prefix meaning in english and batak language is different .Both the languages, have the different prefix with the different meaning for a word. In conclusion, that prefix in English and Batak language are different.